A Casa Civil como estrutura de poder e controle da presidência: gênese, trajetória e o seu desenvolvimento institucional no governo FHC - Lameirão, Camila Romero (2013)
Under an institutional approach, introduced into presidential studies by Terry Moe, this thesis carry out a research about the path of the Casa Civil of the Republic Presidency, and its specific development in Fernando Henrique Cardoso (1995-2002) government. Our aim is examine the organizational changes and, in this scope, the functions and prerogatives given to Casa Civil over time, precisely from its formal establishment, in 1938 during the Estado Novo, until FHC presidency. In this study, we propose the hypothesis that the presidents have used and managed the presidential structure and prerogatives to maximize their control and leadership over the Executive, the parliamentarians, and the Legislative. Having a focus on FHC government, this thesis investigates to what extent it was possible to implement the role and functions that was projected to Casa Civil in this presidential term, especially to take control over the government (Executive) and over the relationship with National Congress. We concluded that the institutional development of the Casa Civil has been associated with the presidential prerogatives powers, arise from the discretionary character of the authoritarian governments (Estado Novo and military regime), and the presidential s roles defined by the federal Constitution of 1988. Based on these prerogatives, we show that the presidents have unilateral decision rights to shape their staff organization and structure that support them to manage and exercise the government in a way more attractive to their interests and political projects